Obstetric complications during the postpartum period, in relation to the new classification of pregnancy at the end of the ACOG, in the hospital of Vitarte, year 2018 - Montenegro Rivera, Eduardo (2021)
Objective: Determine the association between puerperal complications and the classification of Pregnancy to Term of the ACOG, in the Hospital of Vitarte, year 2018. Materials and methods: The study carried out is analytical, retrospective case-type and control. The study population was made up of patients with intermediate postpartum period and who had some complication during this period. It was represented by 268 patients, with 134 cases and 134 controls with a ratio of 1:1. The information was collected from the Clinical Histories and these were: age, degree of instruction, parity, N° CPN, RPM, BMI, hemoglobin, term pregnancy, type of delivery, duration of vaginal delivery, use of oxytocics, induction of labor, complication of J. labor, Apgar and volume of bleeding. Results: The most common type of puerperal complication was puerperal infection 61.19% and puerperal hemorrhage 30.60%. There was no statistical association between Pregnancy to Term and puerperal complication. Of the factors studied, N° insufficient CPN was 4.5 times more likely to present complication as well as other factors such as multiparity, overweight, anemia and the presence of complication during childbirth. Conclusions: It was found that there is no significant association between the classification of pregnancy in its different subclassifications and the presence of complications during puerperium. In terms of developing more complication, develop a specific type of complication and in a differentiated management between one or another classification of E. to term.